The Schools of Czech Minority in Romanian Banat – from their Establishment to the Outbreak of World War II: (historical comparative study) (Theatrum historiae, 2006)
The submitted contribution deals with education of the Czech minority in Romania. The article monitors the period when the first Czech colonists came to Romanian Banat concentrating on their struggle for enlightment and improving the school system up to the establishment of first Czech schools. It aims to show the legal background of Czech school system in Romania. The contribution also deals with the problems that the author processed for the collection of papers about the role of Czech schools abroad (with regard to the former Eastern block).